Food intake of early juvenile western Baltic cod ( Gadus morhua ) during settlement transition - Anton Höper; Nicole Funk; Felix Mittermayer; Axel Temming; Steffen Funk (Journal of Fish Biology, 2026)
This study examines the gut contents of 203 early juvenile Atlantic cod [17–101 mm ± 18.48 mm standard deviation (SD)] from the Western Baltic Sea (ICES Subdivision 22) collected between 2020 and 2022. According to the observed prey (proportion of pelagic, intermediate and benthic items) in the cod guts, settlement transition from a pelagic to a benthic lifestyle is estimated to take place at 46–87 mm cod total length (TL). Copepod species were the preferred prey item of pelagic feeding juvenile cod, dominated by the genus Acartia , which is also the most abundant copepod genus in the area. With increasing cod size, Centropages spp. and Cladocera species were favoured. Intermediate prey consisted mostly of late bivalve veliger larvae. Although a switch from planktonic to intermediate prey was not observable in every cod individual (probably due to differences in prey availability between years and stations), our results showed that especially at the beginning of the demersal life, all examined cod relied almost exclusively on the Cumacean species Diastylis rathkei . Its importance to cod during the settlement transition is in accordance with earlier findings from the same and adjacent areas highlighting it as potential key, but also bottleneck, species for cod recruitment success. Because D. rathkei is highly sensitive to low oxygen conditions, and oxygen minimum zones are spreading in the Western Baltic Sea, the decreasing access to D. rathkei as prey might be a contributing factor to the low recruitment success of cod in recent years.

Effects of starvation and subsequent re-feeding on moulting interval, growth increment and mortality in common brown shrimp (Crangon crangon) - Merten Saathoff; Axel Temming; Robert Perger (Marine Biology, 2025)
The common brown shrimp, Crangon crangon , plays a vital role in the coastal North Sea ecosystems, contributing significantly to the trophic dynamics. This small but highly abundant crustacean is also of economic importance, forming the basis of an approximately 400 vessel strong fishery. Specimens of the common brown shrimp, C. crangon , were deprived of food and subsequently re-fed under controlled conditions (17 ± 1.7 °C, ad libitum feeding) to investigate the effects of starvation with subsequent re-feeding on dry mass accumulation during the intermoult period, mortality and growth. Mortality was negatively affected by starvation, and re-feeding was identified as particularly critical for animal survival, as over 90% of the observed mortality occurred after the onset of re-feeding. Starvation increased the moulting interval and decreased increments after moulting, resulting in a shrinkage of up to 8% in length within 21 days. A correlation between weight loss during starvation and decrease in length was found. The comparison of dry weight conditions between starving animals and field samples suggested that shrinkage must be a more widespread phenomenon in C. crangon than previously assumed. Based on the observations, shrinkage could be identified as a physiological necessity following starvation. Accordingly, it could also occur in other crustacean species in cases where an individual’s dry mass is reduced due to starvation.

Is analysis of otolith microstructure a valid method for investigating early life history of Western Baltic cod? - Rene Plonus; Kate McQueen; Claudia Günther; Steffen Funk; Axel Temming; Uwe Krumme (Marine Biology, 2021)
Daily formation of fish otolith micro-increments is frequently assumed, however applying inferences about timing of life history events and formation of otolith macro-structures requires further validation of the periodicity of micro-increment formation. We analysed micro-increments from Western Baltic cod (WBC, Gadus morhua ) otoliths marked with tetracycline-hydrochloride as part of an age validation study to test the assumption of daily formation of micro-increments. We found that the number of counted micro-increments consistently underestimated the age of cod aged 1 and older. Time at liberty was also underestimated, especially for fish at liberty during winter. In contrast, micro-increment counts of otoliths from wild-caught young-of-the-year (YOY) cod could be used to realistically estimate timing of hatch and translucent zone formation. Under ambient conditions, settlement did not correspond to any visible pattern within the otoliths, but could be inferred from the prey switch observed from stomach content analyses. We therefore conclude that micro-increments can be assumed to form on a daily basis until the first winter, and can therefore be used to investigate early life history of YOY WBC. However, the periodicity of micro-increment formation appears to vary seasonally in older individuals, with the number of micro-increments formed during the winter period being particularly low.

The forgotten feeding ground: patterns in seasonal and depth‐specific food intake of adult cod Gadus morhua in the western Baltic Sea - Steffen Funk; Romain Frelat; Christian Möllmann; Axel Temming; Uwe Krumme (Journal of Fish Biology, 2021)
This study presents the diet composition of western Baltic cod Gadus morhua based on 3150 stomachs sampled year‐round between 2016 and 2017 using angling, gillnetting and bottom trawling, which enhanced the spatio‐temporal coverage of cod habitats. Cod diet composition in shallow areas ( Carcinus maneas . Compared to historic diet data from the 1960s and 1980s (limited to depth >20 m), the contribution of herring Clupea harengus decreased and round goby Neogobius melanostomus occurred as a new prey species. Statistical modelling revealed significant relationships between diet composition, catch depth, fish length and season. Generalized additive modelling identified a negative relationship between catch depth and stomach content weight, suggesting reduced food intake in winter when cod use deeper areas for spawning and during peak summer when cod tend to avoid high water temperatures. The results of this study highlight the importance of shallow coastal areas as major feeding habitats of adult cod in the western Baltic Sea, which were previously unknown because samples were restricted to deeper trawlable areas. The results strongly suggest that historic stomach analyses overestimated the role of forage fish and underestimated the role of invertebrate prey. Eventually, this study shows the importance of a comprehensive habitat coverage for unbiased stomach sampling programmes to provide a more reliable estimation of top predator diet, a key information for food web analyses and multispecies models.

To Fish or Not to Fish – Economic Perspectives of the Pelagic Northeast Atlantic Mackerel and Herring Fishery - Sandra Rybicki; Katell G. Hamon; Sarah Simons; Axel Temming (Frontiers in Marine Science, 2020)

Erratum to: Relationships between feeding, growth and swimming activity of European sprat (Sprattus sprattus L.) post-larvae in the laboratory - Myron A. Peck; Jens-Peter Herrmann; Bianca Ewest; Sven Stäcker; Axel Temming (Environmental Biology of Fishes, 2015)

Relationships between feeding, growth and swimming activity of European sprat (Sprattus sprattus L.) post-larvae in the laboratory - Myron A. Peck; Bianca Ewest; Jens-Peter Herrmann; Fahad A. Al-Misned; M. Golam Mortuza; Sven Stäcker; Axel Temming (Environmental Biology of Fishes, 2015)

The missing link: tidal‐influenced activity a likely candidate to close the migration triangle in brown shrimp C rangon crangon ( C rustacea, D ecapoda) - Marc Hufnagl; Axel Temming; Thomas Pohlmann (Fisheries Oceanography, 2014)
Life cycle closure for species inhabiting areas with daily varying currents but directed net water transport requires specific behavior to minimize losses due to advection of passive drifting life stages. Variations in swimming activity of different‐sized C rangon crangon (15–65 mm total length) were therefore monitored under constant laboratory conditions immediately after being caught in the G erman W adden S ea. Activity of shrimps of different sizes, caught at different seasons, always peaked at times corresponding with ebb tide in the habitat from where they were taken. This behavior was maintained for several days if no external stimuli were present but shifted to night activity if a light–dark cycle was provided. The observed behavior/activity pattern was included in a coupled hydrodynamic and individual‐based model ( IBM ) and the shift in the location of a shrimp cohort was monitored over time. Performance of ebb tide activity not only allowed the shrimps to reach the preferred deeper winter and spawning areas but also allowed them to migrate against the dominating current from eastern nurseries to more western located spawning areas. Passively drifting larvae released at these locations and later larval and juvenile stages that perform flood tide transport can reach the nurseries again. This links the nurseries and adult spawning grounds and closes the migration triangle.

Lower thermal capacity limits of the common brown shrimp (Crangon crangon, L.) - Stefan Reiser; Jens-Peter Herrmann; Thomas Neudecker; Axel Temming (Marine Biology, 2014)

Hermaphroditism in brown shrimp: lessons from field data and modelling - Marc Hufnagl; Axel Temming; Andreas Dänhardt (Marine Biology, 2010)

Predation Hot Spots: Large Scale Impact of Local Aggregations - Axel Temming; Jens Floeter; Siegfried Ehrich (Ecosystems, 2007)

Linking growth to environmental histories in central Baltic young‐of‐the‐year sprat, Sprattus sprattus : an approach based on otolith microstructure analysis and hydrodynamic modelling - HANNES BAUMANN; HANS‐HARALD HINRICHSEN; RUDI VOSS; DANIEL STEPPUTTIS; WLODZIMIERZ GRYGIEL; LOTTE W. CLAUSEN; AXEL TEMMING (Fisheries Oceanography, 2006)
Otolith microstructure analysis and hydrodynamic modelling were combined to study growth patterns in young‐of‐the‐year (YoY) sprat, Sprattus sprattus , which were sampled in October 2002 in the central Baltic Sea. The observed ‘window of survival’, approximated by the distribution of back‐calculated days of first feeding (DFF), was narrow compared to the extended spawning season of sprat in the Baltic Sea (mean± SD = 22 June ± 14.1 days) and indicated that only individuals born in summer survived until October 2002. Within the group of survivors, individuals born later in the season exhibited faster larval, but more rapidly decreasing juvenile growth rates than earlier born conspecifics. Back‐calculated larval growth rates of survivors (0.48–0.69 mm day −1 ) were notably higher than those previously reported for average larval sprat populations, suggesting that the YoY population was predominantly comprised of individuals which grew faster during the larval stage. Daily mean temperatures, experienced across the entire YoY population, were derived from Lagrangian particle simulations and correlated with (1) detrended otolith growth and (2) back‐calculated, daily somatic growth rates of survivors. The results showed that abrupt changes in ambient temperature can be detected in the seasonal pattern of otolith growth, and that higher temperatures led to significantly faster growth throughout the entire age range of YoY sprat.

Life cycle of Crangon crangon in the North Sea: a simulation of the timing of recruitment as a function of the seasonal temperature signal - Axel Temming; Ulrich Damm (Fisheries Oceanography, 2002)
The brown shrimp C. crangon supports a large commercial fishery in British, Belgian, Dutch, German and Danish waters. It produces eggs throughout the year with two seasonal peaks in summer and winter, respectively. Uncertainty exists with regard to the relative importance of the two egg production seasons for the mass invasion of juvenile recruits of 10–20 mm length in May/June, which is the dominant seasonal signal in the German and Dutch Wadden Sea, and which is presumed to grow into the exploitable stock by the autumn, causing the typical rise of commercial catches at that time of the year. A simulation model was developed that predicts the daily abundance of juvenile recruits attaining a given length, typically in the range of 10–20 mm. The model uses: (i) experimental data on the development times of eggs and larvae and the growth rates of juveniles; (ii) field data on the seasonal temperature cycle in different years (1986, 1992 and 1993 or mean conditions) and areas (German and Dutch Wadden Sea) of the North Sea; and (iii) a calculated index of the relative seasonal egg production intensity of adult C. crangon . Predictions of the simulations are compared with field observations on the seasonal occurrence of juvenile recruits in the German and Dutch Wadden Sea. Using temperature data from German waters, in the simulations peak recruitment was predicted to occur 1–2 months later than that observed in the field. However, if seasonal temperature data from Dutch waters were used, the predicted time of the first mass occurrence of recruits matched the field observations more closely. Simulations revealed that the first mass invasion of juveniles originates almost entirely from the winter egg production. It was also found that the simulated recruitment is condensed into a peak, which is narrower after a cold winter.